2013
DOI: 10.1097/wnr.0b013e328363148c
|View full text |Cite
|
Sign up to set email alerts
|

Altered motor network functional connectivity in amyotrophic lateral sclerosis

Abstract: Resting-state functional MRI provides a viable tool for assessing brain dysfunctions in amyotrophic lateral sclerosis (ALS) without using explicit tasks. Altered resting brain functional connectivity (FC) in ALS has been reported in several studies but with large discrepancies in terms of the alteration directions. The purpose of this study was to provide new evidence for the resting FC disruptions in ALS. We focused on FC in the motor network as motor dysfunctions are a hallmark of ALS pathology. To test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 9 publications
5
34
0
Order By: Relevance
“…Two studies found reduced connectivity in this network, 56,57 while another reported a mixed pattern of both increased and reduced connectivity. 58,59 Findings in ALS populations have been more consistent in terms of structural connectivity disruption. There is extensive evidence of reduced FA in the CST and corresponding motor network, [60][61][62][63][64][65][66][67][68] and of an association between sensorimotor network damage and disease severity.…”
Section: Behavioural Variant Frontotemporal Dementiamentioning
confidence: 88%
See 1 more Smart Citation
“…Two studies found reduced connectivity in this network, 56,57 while another reported a mixed pattern of both increased and reduced connectivity. 58,59 Findings in ALS populations have been more consistent in terms of structural connectivity disruption. There is extensive evidence of reduced FA in the CST and corresponding motor network, [60][61][62][63][64][65][66][67][68] and of an association between sensorimotor network damage and disease severity.…”
Section: Behavioural Variant Frontotemporal Dementiamentioning
confidence: 88%
“…30,44,58,76,78,102 Other authors have also endorsed the 'compensatory theory' , but with little evidence. 57,84,87 Importantly, some studies showed an inverse relationship; that is, higher connectivity correlated with more-severe clinical symptoms 35,44 or faster disease progression, 58,60,61,83 suggesting a maladaptive and/or pathogenic mechanism rather than a compensatory phenomenon. A maladaptive response might reflect an unsuccessful attempt to recruit preserved neuronal areas to compensate for pathology, as well as a disrupted excitatory-inhibitory balance of damaged networks due to impending pathological processes.…”
Section: Frontotemporal Dementiamentioning
confidence: 99%
“…Changes in functional connectivity could also result from an alteration in the local excitation/inhibition balance due to the dysfunction of inhibitory interneurons (Douaud et al, 2011): in fact, pathological studies have found that calbindin-positive GABAergic interneurons undergo degeneration in ALS (Maekawa et al, 2004), lending support to the hypothesis that loss of inhibitory tone contributes to clinical dysfunction in ALS (Turner and Kiernan, 2012). The two models are actually not mutually exclusive: the pattern of either increased either decreased connectivity in resting-state (Jelsone-Swain et al, 2010; Mohammadi et al, 2009; Zhou et al, 2013; Agosta et al, 2013; Douaud et al, 2011) and task-based fMRI (Heimrath et al, 2014; Konrad et al, 2002; Lulé et al, 2009) may be the result of ongoing degeneration and loss of axons (Dadon-Nachum et al, 2011; Sarica et al, 2014) accompanied by potentially compensative phenomenon (Bernier et al, 2017). The observed increase in projection from cortical and subcortical areas might be an early adaptive response to ongoing cell dysfunction up to the point where a critical cell loss is reached and a disconnection syndrome begins to emerge (Gorges et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings of FC abnormalities, also mostly related to the motor system, however, are inconsistent. Reports of enhanced sensorimotor network connectivity Douaud et al, 2011], reduced premotor FC [Mohammadi et al, 2009] or a combination of increased and decreased FC [Zhou et al, 2013], leave the relation between changes in SC and FC an open question.…”
Section: Introductionmentioning
confidence: 99%